Microfinance: A comprehensive review of the existing literature - James C. Brau; Gary M. Woller (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
Although the word finance is in the term microfinance, and the core elements of microfinance are those of the finance discipline, microfinance has yet to break into the mainstream or entrepreneurial finance literature. The purpose of this article is to introduce the finance academic community to the discipline of microfinance and microfinance institutions (MFIs). We provide a comprehensive review of over 350 articles and address the issues of MFI sustainability, products and services, management practices, clientele targeting, regulation and policy, and impact assessment.
Keywords: 650